Effects of Flooring Types on Growth Performance, Behaviour and Health of Dairy Calves - Yanar, M; Diler, A; Ozdemir, VF; Aydin, R; Koçyiğit, R; Gul, MH (Journal of the Hellenic Veterinary Medical Society, 2022)
In this study, perforated rubber mats (PRM), concrete floor bedded with long wheat straw (CLS and concrete floor bedded with wheat straw (CS) were compared as flooring types for dairy calves. Growth, feed efficiency ratio, gains in body measurements, some behavioural activities as well as faecal scores, bedding scores and calf’s cleanliness scores of the dairy calves were evaluated for 6 months. Overall growth rate differed significantly due to types of floor, and total weight gains of the dairy calves in PRM group was 7.0% and 16.0% higher than those of calves in CLS and CS groups respectively. However, differences with regard to the amount of dry matter of milk, concentrate as well as total dry matter of the feeds consumed per kg of weight gain during pre-weaning and post-weaning periods among the PRM, CS and CLS groups were not statistically significant. When, gains in linear body measurements were evaluated, total gains in height at withers, body length, chest depth and heart girth of the calves in PRM group were superior to those in CLS and CS groups. The calves in PRM group had high growth rate along with high percentage of time spent for lying behaviour which is one the most significant activities among the behaviours of the calves. The calves kept on PRM group exhibited 52.6% and 45.5% higher percentage of time spent for lying behaviour than those in CS and CLS groups respectively. Data regarding the bedding scores and calf’s cleanliness scores also revealed that the PRM flooring was the cleanest and driest one compared to the other flooring types, and the calves in the PRM group were cleaner than those in CLS and CS groups. Calves in PRM group exhibited significantly (P<0.01) lover faecal consistency scores than those in CLS and CS groups. In conclusion, based upon growth rate, feed efficiency ratio, behavioural parameters as well as the bedding scores, calf’s cleanliness scores and faecal consistency scores, PRM is preferable to CLS and CS floorings for individual dairy calves’ pens.